Modeling athletic career of football players: Implications for career management and retirement - Monteiro, R.; Monteiro, D.; Torregrossa, M.; Travassos, B. (International Journal of Sports Science & Coaching, 2023)
This study aimed to identify Career Indicators (CIs) over the stages of career development (Initiation/Development, Mastery, and Discontinuation stages) in the retirement stage of Portuguese football players. Three thousand five hundred retired Portuguese football players that played between 1960 and 2018 were considered in this study. A path analysis was performed to identify the standardized direct and indirect effects of the CI at each stage of career development, on Portuguese football players` retirement age. The proposed model highlighted that the relationship between the CI number of seasons as a youth player, number of seasons as a youth player in top 3 clubs, age of first registration as a senior player, number of seasons as a senior player, number of seasons as a senior player in top 3 clubs, number of total games as a senior player, age of the last best result age achieved, number of games in the retirement season, and discontinuation stage length contribute to explain 40% of the retirement age of Portuguese football players. Results allowed the understanding of the influence of each stage of career development on career length. According to the Holistic Athletic Career Model, it was the first attempt to create a predictive model of CI of athletic variables. Further research should be developed to incorporate some mediator variables such as players` performance levels and achievement to improve the explanation of the development of football players` careers and retirement.